PENAHANAN IJAZAH PEKERJA OLEH PEMBERI KERJA DALAM PERSPEKTIF TEORI KEADILAN BERMARTABAT [Detention of Diploma Certificates by Employers from the Perspective of the Dignified-Justice Theory] - Ellora Sukardi; Debora Pasaribu; Vanessa Xavieree Kaliye (Fakultas Hukum, Universitas Pelita Harapan | Lippo Karawaci, Tangerang, 2021)
A diploma certificate is a document that has a value to a person has after he/she has completed one stage of education. A diploma certificate is useful for job applications depending on the qualifications that were acquired. However, there is a custom in society where employers withhold their workers’ diplomas for a specified period of service. Withholding diplomas sometimes gives workers disadvantages because of the lack of security guarantee and also it creates greater risk and responsibility for employers. This research is conducted with juridical-normative methods. In terms of the Dignified Justice Theory which was coined by Teguh Prasetyo, the theory focuses on the concept of humanizing humans (nge wongke wong), therefore detention of diplomas that is carried out unilaterally by the employer without any guarantee of security protection for the workers’ diploma is considered as unfair and violates the rights or harms workers. In this case, it is necessary to have detailed clauses set out in the work agreement. In addition, the employer must have a Standard Operating Procedure regarding the holding of diplomas to ensure the security as long as they are kept.Bahasa Indonesia Abstrak: Ijazah merupakan dokumen yang bernilai bagi seseorang setelah yang bersangkutan menyelesaikan satu tahapan pendidikan. Ijazah berguna untuk melamar pekerjaan sesuai dengan kualifikasi yang dimiliki pemegang ijazah tersebut. Namun, terdapat sebuah kebiasaan di masyarakat dimana pemberi kerja menahan ijazah pekerjanya dalam masa kerja yang ditentukan. Penahanan ijazah terkadang merugikan pekerja dikarenakan keamanan ijazah yang kurang terjamin serta menimbulkan risiko dan tanggung jawab yang lebih besar pada pemberi kerja untuk menyimpan dokumen berharga tersebut. Metode yang digunakan adalah yuridis-normatif. Ditinjau dari Teori Keadilan Bermartabat yang dicetuskan oleh Teguh Prasetyo, yang menitikberatkan pada konsep memanusiakan manusia (nge wongke wong), penahanan ijazah yang dilakukan secara sepihak oleh pemberi kerja tanpa adanya jaminan atas perlindungan keamanan bagi ijazah pekerja dinilai kurang adil dan melanggar hak atau merugikan pekerja. Dalam hal ini, perlu adanya klausul yang terperinci yang dituangkan di dalam perjanjian kerja. Selain itu, pemberi kerja harus memiliki prosedur pelaksanaan mengenai penahanan ijazah untuk menjamin keamanan ijazah pekerja selama ijazah tersebut disimpan oleh pemberi kerja.